Energy generation from revolving door - Ahamed, Raju; Rashid, Muhammad Mahbubur; Islam, Jahidul; Javed, Asief; Md Yusof, Hazlina (Indian Society for Education and Environment, 2016)
To meet energy demand, renewable energy and some unconventional source of energy can provide the necessary amount of clean energy for climate stabilization and reduce the consumption of fossil fuel. In this paper, prospect and feasibility of power generation by using revolving door has been investigated. The objectives of this paper is to designand fabricated of a prototype revolving door which can generate energy by amplifying the initial RPM of door shaft. Gear, pinion and motor mechanismare used as an energy generation part of the proposed revolving door. Different data are taken by applying various conditions despite the RPM in practice. The prototype can produce 4 volts and the total output depends on frequency of people passing through the door. By this arrangement, the minimum output power is obtained nearly 1.564 watts at RPM 13 and the maximum output power is found about 2.6 watts at RPM 23.